Unveiling the Landscape of Traumatic Spinal Injuries in a Sub-Saharan African Setting: A Hospital-Based Cross-Sectional Study - Takoutsing, Berjo; Esene, Ignatius; Kwasseu, Gaetan Konfo; Nkouonlack, Cyrille Duquesne; Fokam, Pius; Chichom-Mefire, Alain (WFNS Journal, 2025)
Traumatic spinal injury (TSI) is a devastating neurological condition that imposes a substantial economic burden on victims, families, and healthcare systems. While the prevalence and patterns of TSI can vary, its landscape in Cameroon remains underexplored.We performed a cross-sectional study to determine the prevalence and sociodemographic, prehospital, and clinical patterns of TSI at the two major referral hospitals in the Southwest Region (SWR) of Cameroon; Buea and Limbe Regional Hospitals, from 2017 to 2021. Descriptive statistics were used to summarize the data, and the chi-square test was applied for bivariate comparisons.We identified 74 hospital admissions for TSI, with a hospital prevalence of 1% (95% CI: 0.8–1.2%). The most affected were males (79.2%), those aged between 25 and 44 years (55.6%), farmers (30.6%), married individuals (54.2%), and those living in a town different from our two centers (72.2%). Eighty percent of patients presenting <24 hours following the injury presented directly, while 87% of those presenting ≥24 hours presented as a referral (p < 0.001). All patients were transported from the sites of injury in a nonmedicalized vehicle. The most prevalent etiology was falls (43.7%), and the cervical spine was mostly affected (44.4%). Frankel's A and D grades were more common severities during admission (23.6 and 23.6%). More than half (66.7%) had an incomplete TSI.TSIs constitute a significant burden in the SWR, with significant prehospital delays. Enforcing safety measures, and strengthening referral and emergency care systems, could help mitigate its impact.
Keywords: Cameroon; prevalence; retrospective studies; spinal cord; trauma